PEMBUATAN ELEKTRODA SELEKTIF ION PB (II) BERMEMBRAN HOMOGEN - Yusiasih, Retno
The homogenous-membrane for lead (II)-ion selected electrode has been made. This type of membrane consists of active material, PbS - Ag2S, which is prepared by the precipitation method and then is continously pressed. The result of the research indicated that a suitable membrane will be achieved in proportion of mole percentage of PbS:Ag2S = 30:70,which is result from 50 mL of solution which contains a mixture of 0,012 mole Pb(NO3)2 and 0,056 mole AgNO3 with 80 mL of solution Na2S 1 M. The membrane is achieved by repressed of 400 kg/cmÂ² to 600 kg/cmÂ². In that condition, the homogenous-membrane lead (II)-ion selective electrode is Nernstient, that is, 29,72 mV/decade with a measurement range of between l0-4M - 10-1M, time response is 150 seconds. Although the method of determination of selectivity coefficient has not a consistent value, those interference ions Cu e+ and Ag l+ are studied indicated have an effect of interference.